2016
DOI: 10.1080/15599612.2016.1166305
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based dynamic tracking of an untethered ferromagnetic microcapsule navigating in liquid

Abstract: The propulsion of ferromagnetic objects by means of MRI gradients is a promising approach to enable new forms of therapy. In this work, necessary techniques are presented to make this approach work. This includes path planning algorithms working on MRI data, ferromagnetic artifact imaging and a tracking algorithm which delivers position feedback for the ferromagnetic objects, and a propulsion sequence to enable interleaved magnetic propulsion and imaging. Using a dedicated software environment, integrating pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 29 publications
(43 reference statements)
0
48
0
Order By: Relevance
“…The most correlated slice gives the out‐of‐plane distance of the robot to the slice of the image. Later, Dahmen et al demonstrated that the template stack matching method can be performed faster by k ‐space reduction …”
Section: Localization and Tracking With Mrimentioning
confidence: 99%
See 4 more Smart Citations
“…The most correlated slice gives the out‐of‐plane distance of the robot to the slice of the image. Later, Dahmen et al demonstrated that the template stack matching method can be performed faster by k ‐space reduction …”
Section: Localization and Tracking With Mrimentioning
confidence: 99%
“…Tracking and localization data acquired by MRI systems can be around 100 Hz when simultaneous imaging and actuation sequences are used; however, it lacks the true position information since these frequencies can be achieved when only single 1D line scans are used. Typically, the feedback rates are at around 10–30 Hz for sequential actuation and tracking sequences . Unlike standard robotic approaches, where high‐speed cameras or high‐performance computers provide very accurate estimation at much higher frequencies, the limited feedback data could be one of the challenges for medical applications under highly dynamic environments.…”
Section: Future Outlook and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations